Exploring black South African men's lived experiences of being fathered - Rasebitse, Karabo (Rhodes University, Faculty of Humanities, Department of Psychology)
There is a lack of research studies in South Africa that explore young men's lived experiences of being fathered. The aim of this study focused on exploring how Black South African men construct and understand their own lived experiences of being fathered by their biological father. This research study is situated within a social constructionism methodology and theoretical framework. Data were collected using semi-structured interviews with young men between the ages of 18-24. Data were analysed using thematic analysis as a way of analysing participants' stories. Three central themes with subthemes emerged. The main themes regarded the father behaviour, fatherly roles and participants' constructions of fatherhood. The study argues that fatherhood is a social construct based on participants' lived experiences. Participants in this research still view fatherhood from cultural discourses, such as the provider/protector and a moral guider/role to construct fatherhood.
Keywords: Fatherhood -- South Africa; Fathers and sons -- South Africa Psychological aspects; Masculinity Social aspects -- South Africa; Hegemony -- South Africa; Social constructionism -- South Africa; Culture; Men, Black Attitudes -- South Africa